Blood alone ebook - Benn, James R. (Billy Boyle World War II Mystery, 2008)
Praise for the Billy Boyle series: “The brash kid from Southie is still open, direct and fearless in his manner (and in his wonderfully loose-jointed use of the English language) and in no danger of losing his cover as a ‘happy-go-lucky Yank.’ But even amid the excitement of the spirited wartime storytelling, Benn allows Boyle’s experiences to change him in ways both subtle and dramatic.”—Marilyn Stasio, The New York Times Book Review “Thoroughly enjoyable.”— The Seattle Times “This series brings WWII alive.”— Deadly Pleasures “Great fun. Benn knows his war history.”— The Globe and Mail “Kudos to author Benn . . . and here’s hoping that Billy will continue to make his way through his Uncle Ike’s world for many titles to come.”—Bookslut.com Billy Boyle awakens in a field hospital in Sicily with amnesia. In his pocket is a yellow silk handkerchief embroidered with the initial L. Gradually he remembers: he has been sent ashore in advance of the troops with this token from Lucky Luciano to contact the head of the Sicilian Mafia. But he must also thwart a murderous band of counterfeiters of Army scrip led by Vito Genovese. James R. Benn is the author of Billy Boyle: A World War II Mystery , selected by Book Sense as one of the top five mysteries of 2006 and nominated for a Dilys Award. The First Wave was a Book Sense Notable title. Benn is a librarian and lives in Hadlyme, Connecticut.